Persepsi dan Partisipasi Gabungan Kelompok Tani Hutan Belek Lerek Terhadap Sistem Hutan Kemasyarakatan (Studi Kasus HKm Desa Baolangu, Kabupaten Lembata, Provinsi Nusa Tenggara Timur) - Vinsensus Dominggus Dolet; Ludji Michael Riwu Kaho; Nixon Rammang; Maria M. E. Purnama (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2026)
The community's decision to participate or not in an activity is influenced by subjective factors such as the community's own perception of the activity (Ngakan, 2006). The importance of community perceptions about the purpose and benefits of community forestry as a system in forestry to be managed properly and correctly so as to achieve goals in preserving and prospering the community (Heryatna et al., 2015). The Baolangu Village Community Forest Utilization Business Permit was granted to the Belek Lerek Forest Farmer Group Association consisting of 5 forest farmer groups covering an area of + 150 Ha in the Protected Forest area in Baolangu Village. Of the 5 forest farmer groups formed, 1 forest farmer group remains active but in general the community continues to manage their Community Forest land. The purpose of this study was to determine the positive perceptions of the community about Community Forests that influence community participation in Community Forest management. The technique of taking respondents in this study used the census method, namely taking one population group as a whole sample and using a structured questionnaire as a data collection tool with a total of 77 respondents. The measurement scale used is the Likert scale model. The results showed that community participation of the Belek Lerek Forest Farmer Group Association in the implementation stage of the Community Forest was high (58.77%), and the utilization stage was high (61.29%), because the community managed their respective Community Forest areas by planting plantation crops, food and horticulture, the results of which were not only for consumption but also for sale. This is influenced by the community's positive perception of the Baolangu Village Community Forest, where the IUPHKm provides certainty of access rights to the community to participate in managing the forest area, the existence of the Community Forest can increase household income and community empowerment carried out by related institutions such as KPH Lembata is running well.